2022
DOI: 10.3390/su14042277
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the General Public in Urban and Rural Areas in Southern Japan

Abstract: Urban and rural areas are situated in contrasting physical and social settings, which influence their levels of exposure as well as their preventive behaviors in response to the COVID-19 outbreak. The study investigated whether there were differences between the areas regarding the levels of difficulty and anxiety felt by the general public during the first wave of COVID-19 in April and May 2020. We conducted an online questionnaire in Fukuoka and Kumamoto Prefecture in southern Japan via a private research co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…From the findings, more than 42% of residents received a third dose of COVID-19 vaccination because COVID-19 campaigns encouraged residents in areas with high cases of COVID-19 infection to receive a robust dose of the vaccine against COVID-19 in order to create herd immunity, as promoted by the Thai government [29]. However, the number of infected residents was increasing in this area, and 53.2% of residents in this area had had COVID-19 infections because of a high level of exposure to the virus and the social-economic situation of dealing with the outbreak [19]. Suitable policies and campaigns to reduce the number of COVID-19 infections among residents in this area should be urgently implemented to reduce the number of COVID-19 infections in extreme situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the findings, more than 42% of residents received a third dose of COVID-19 vaccination because COVID-19 campaigns encouraged residents in areas with high cases of COVID-19 infection to receive a robust dose of the vaccine against COVID-19 in order to create herd immunity, as promoted by the Thai government [29]. However, the number of infected residents was increasing in this area, and 53.2% of residents in this area had had COVID-19 infections because of a high level of exposure to the virus and the social-economic situation of dealing with the outbreak [19]. Suitable policies and campaigns to reduce the number of COVID-19 infections among residents in this area should be urgently implemented to reduce the number of COVID-19 infections in extreme situations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study of Kunno et al [34] found that the level of good (50.9%) and poor (49.1%) attitudes toward COVID-19 among healthcare workers in the urban community of Bangkok, Thailand, were approximated. The reason for this result was that urban inhabitants are presumably more exposed to COVID-19, with an increasing number of COVID cases and social activities with a high risk of viral transmission in urban areas [19]. Hence, a poor attitude toward COVID-19 among Thai residents was found in endemic locations, along with a situation of panic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire as the measurement tool in this study was a modified version of a previous survey [ 38 , 39 , 40 ]. The pre-test process of the questionnaire was undertaken by 30 populations in another province for testing the validity and reliability of the measurement tool, with a 0.75 Cronbach’s alpha coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 pandemic has had varying impacts on people from different walks of life, including sports in the sense of mass sports competitions [ 1 ]. Many major sporting events were canceled and others were postponed; those that ultimately took place, such as the Olympic Games in Tokyo, were held under a total sanitation regime and virtually without an audience [ 2 , 3 , 4 ]. The pandemic restrictions and the SARS-CoV-2 virus affected not only the participation of elite athletes in sporting events but also their daily training sessions, which either could not take place or occurred irregularly as a result of the closure of sports facilities and, above all, as a result of COVID-19 infections among athletes themselves, as well as their coaches and other colleagues [ 5 ].…”
Section: Introductionmentioning
confidence: 99%